Reactions of Nitroxides, Part 17. Synthesis, Fungistatic and Bacteriostatic Activity of Novel Five- and Six-Membered Nitroxyl Selenoureas and Selenocarbamates - Zakrzewski, Jerzy (Molecules, 2019)
The reactions of 3-isoselenocyanato-2,2,5,5-tetramethylpyrrolidine-1-oxyl, 3-isoselenocyanatomethyl-2,2,5,5-tetramethyl-3-pyrrolidine-1-oxyl, and 4-isoselenocyanato-2,2,6,6-tetramethylpiperidine-1-oxyl with selected amines and alcohols give the corresponding novel nitroxyl selenoureas and selenocarbamates, all bearing a nitroxyl moiety. Synthesized selenoureas and selenocarbamates show significant activity against pathogenic fungi and bacteria. In contrast to piperidine nitroxides, pyrrolidine, five-membered nitroxyl selenoureas and selenocarbamates show excellent antifungal and antibacterial activity against pathogenic fungi and bacteria, respectively.